Synthesis and biological assessment of folate-accepted developer 99mTc-DTPA-folate-polymer. Issue 10 (15th May 2016) - Chen, Fei; Shao, Kejing; Zhu, Bao; Jiang, Mengjun
Graphical abstract: Abstract: A novel cancer-targetable folate-poly(2-hydroxyethyl methacrylate) (PFDH) copolymer containing DTPA segment was prepared by conventional chemical synthesis and labeled with 99m Tc subsequently. The 99m Tc-labled PFDH could be produced easily with high radiochemical yield of 91% and radiochemical purity of 95%. The Log  P octanol–water value for the 99m Tc-labled PFDH was −2.19 and the radiotracer was stable in phosphate-buffered saline and human serum for 2 h (>95% in PBS or ∼90% in human serum). To investigate 99m Tc-labled PFDH tumor targeting, the in vitro and in vivo stability, cell uptake, in vivo biodistribution, and SPECT imaging were evaluated, respectively. These preliminary results strongly suggest that the novel folate conjugated dendrimer maybe developed to be potential for delivery of therapeutic radionuclides.